2014
DOI: 10.4172/2167-0412.1000e152
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fingerprinting of Medicinal and Aromatic Plant Extracts: HPTLC Bioautographic Assays as Preliminary Research Tool to Match Chemical and Biological Properties

Abstract: Chemical plant fingerprinting generally identifies the distribution of compounds within a plant matrix defining its chemical imaging in relation to the different extraction approach adopted. The chemical picture obtained with fingerprinting target needs to represent the highest number of chemical compounds as possible, giving the most realistic portrait of the chemical identity of the plant matrix. The fingerprinting of plant matrices is a research approach aimed to point out chemical evidences related to biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The chemical picture obtained from fingerprint represents the type of ecosphere where the plants have grown. The different secondary metabolites present in the plants may vary in quantity and quality depending on its growing conditions [29]. Therefore, in the present work, the HPTLC fingerprint profile of the essential oils of T. serpyllum grown at different agro-climatic zones has been developed.…”
Section: High-performance Thin-layer Chromatography (Hptlc) Fingerprints Of Essential Oils From Different Locationsmentioning
confidence: 99%
“…The chemical picture obtained from fingerprint represents the type of ecosphere where the plants have grown. The different secondary metabolites present in the plants may vary in quantity and quality depending on its growing conditions [29]. Therefore, in the present work, the HPTLC fingerprint profile of the essential oils of T. serpyllum grown at different agro-climatic zones has been developed.…”
Section: High-performance Thin-layer Chromatography (Hptlc) Fingerprints Of Essential Oils From Different Locationsmentioning
confidence: 99%
“…Plants are sources of huge number of bioactive lead/scaffolds with therapeutic and nutraceutical importance. Bioautography is a fast technique that allows us to identify and isolate bioactive fractions/compounds in never previously studied plant extracts by employing a suitable chromatographic process followed by a biological detection system [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive plants collected at different time periods may considerably differ in their chemical components, thereby resulting in varied chemical profiles (Mera et al, 2019 ). Guerrini and Sacchetti ( 2014 ) reported that the type of plant UV fingerprint is dependent on particular environmental conditions to which the plant is exposed. Genetic and environmental factors, alone or sometimes in combination, influence the metabolic pathways and produce different patterns of chemical composition, thereby leading to variations in fingerprint (Guerrini and Sacchetti, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Guerrini and Sacchetti ( 2014 ) reported that the type of plant UV fingerprint is dependent on particular environmental conditions to which the plant is exposed. Genetic and environmental factors, alone or sometimes in combination, influence the metabolic pathways and produce different patterns of chemical composition, thereby leading to variations in fingerprint (Guerrini and Sacchetti, 2014 ). Therefore, on the basis of the results of the present study, it could be speculated that a high accumulation of secondary metabolites favored the growth of L. camara , P. hysterophorus , A. conyzoides , and R. communis plants under adverse conditions.…”
Section: Resultsmentioning
confidence: 99%